Mucuna chiapaneca (Leguminosae—Papilionoideae) a new species from Mexico - Sousa, Mario; Moura, Tania Maria De (Phytotaxa, 2016)
Mucuna chiapaneca a new species from Chiapas, Mexico is here described, and illustrated. Six species of Mucuna occur in Mexico, two of them are endemic. A table is provided giving the diagnostic characteristics among the six species.